PENGEMBANGAN SAYURAN VERTIKULTUR MELALUI PEMBERDAYAAN MAJELIS TAKLIM DI KELURAHAN PAMPANG KOTA MAKASSAR - Syam, Netty (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2018)
The actualization of the commitment of the Muslim University of Indonesia (UMI) that caresabout the environment is manifested by the efforts of community development in the village ofPampang located adjacent to the campus of UMI, conducted through the application of technology.The objectives of the technology implementation activities are (1) to provide training to womenreligious groups (Majelis Taklim) in Pampang on environmental hygiene, sorting and processingwaste for composting for vegetable cultivation; (2) provide vegetable training and skills byVerticulture system to women's religious groups (Majelis Taklim) in Pampang so that communitygroups become more economically independent. The two types of activities are the main activitiesgiven to women's religious groups (Majelis Taklim) to utilize their free time. Both types ofactivities received positive responses from the trainees and the accompaniment reflected in theirattendance and antuasiame responses in each meeting. Organic waste processing activities need tobe increased into business scale which will also increase the family income and also support theMakassar city government program.